Biotechnology applications for banana and plantain improvement: Proceedings of a workshop, 27-31 January 1992, San José, Costa Rica - International Network for the Improvement of Banana and Plantain (1993)
These proceedings are divided into four sections: non-conventional strategies for producing banana and plantain resistant to pathogens and pests (10 papers, covering genetic maps, transformation, identifying and generating resistance, and cross-pollination breeding); in vitro strategies for Musa (10 papers, covering germplasm handling, genetic improvement and somaclonal variation); technology transfer (1 paper); and recommendations of working groups on the topics covered in the first 3 sections. (Abstract © CAB ABSTRACTS, CAB International)